The acute effect in performing common range of motion tests in healthy young adults: a prospective study - F. Holzgreve (Nature Portfolio, 2020)
Abstract In the application of range of motion (ROM) tests there is little agreement on the number of repetitions to be measured and the number of preceding warm-up protocols. In stretch training a plateau in ROM gains can be seen after four to five repetitions. With increasing number of repetitions, the gain in ROM is reduced. This study examines the question of whether such an effect occurs in common ROM tests. Twenty-two healthy sport students (10 m/12 f.) with an average age of 25.3 ± 1.94 years (average height 174.1 ± 9.8 cm; weight 66.6 ± 11.3 kg and BMI 21.9 ± 2.0 kg/cm2) volunteered in this study. Each subject performed five ROM tests in a randomized order—measured either via a tape measure or a digital inclinometer: Tape measure was used to evaluate the Fingertip-to-Floor test (FtF) and the Lateral Inclination test (LI). Retroflexion of the trunk modified after Janda (RF), Thomas test (TT) and a Shoulder test modified after Janda (ST) were evaluated with a digital inclinometer. In order to show general acute effects within 20 repetitions we performed ANOVA/Friedman-test with multiple comparisons. A non-linear regression was then performed to identify a plateau formation. Significance level was set at 5%. In seven out of eight ROM tests (five tests in total with three tests measured both left and right sides) significant flexibility gains were observed (FtF: p < 0.001; LI-left/right: p < 0.001/0.001; RF: p = 0.009; ST-left/right: p < 0.001/p = 0.003; TT-left: p < 0.001). A non-linear regression with random effects was successfully applied on FtF, RF, LI-left/right, ST-left and TT-left and thus, indicate a gradual decline in the amount of gained ROM. An acute effect was observed in most ROM tests, which is characterized by a gradual decline of ROM gain. For those tests, we can state that the acute effect described in the stretching literature also applies to the performance of typical ROM tests. Since a non-linear behavior was shown, it is the decision of the practitioner to weigh up between measurement accuracy and expenditure. Researchers and practitioners should consider this when applying ROM assessments to healthy young adults.